Soot inception: A DFT study of σ and π dimerization of resonantly stabilized aromatic radicals. (1st November 2020) - Gentile, Francesco Silvio; Picca, Francesca; De Falco, Gianluigi; Commodo, Mario; Minutolo, Patrizia; Causà, Mauro; D'Anna, Andrea
Abstract: Recent advances in the soot studies have shown experimental evidences of π-radicals and cross-linked structures among the molecular constituents of just-nucleated soot particles. π-radicals could have an important role in particle nucleation by increasing the binding energy between polycyclic aromatic hydrocarbons with respect to pure van der Waals interactions. In this work we use density functional theory by Grimme D3 dispersion correction (DFT-D3) with hybrid functional and localized Gaussian basis set (B3LYP/6-31G**) to analyze and classify the clustering behaviors of two aromatic radicals visualized experimentally by atomic force microscopy (Commodo et al. Combust. Flame 205: 154–164, 2019). These aromatic radicals have different topological structures and delocalization of the unpaired electron. The binding energy and energy bandgap characteristics of the clusters are calculated. The theoretical results show a different clustering behavior for the two aromatic radicals. The one with a partial localization of the unpaired electron tends to form a σ-dimer; conversely, the radical with a greater delocalization of the unpaired electron leads to π-stacking formation with a slight overbinding of few kcal mol −1 with respect to pure van der Waals interactions and a marked lowering of the energy bandgap. The formation of π-stacking induced by delocalized π-radicals could in part explain some spectroscopic evidences observed during soot nucleation.